THE EFFECT OF STREET LIGHTING TAX, HOTEL TAX, AND RESTAURANT TAX ON REGIONAL ORIGINAL INCOME - Sefnat Aristarkus Tang (Jurnal Akuntansi dan Pajak, 2023)
Regional Original Revenue (PAD) is regional revenue originating from regional economic sources in the form of taxes, levies, separated wealth management results, and other legitimate PAD. This study aims to determine the role of the Street Lighting Tax (PPJ), Hotel Tax (PH), and Restaurant Tax (PR) in the PAD of Alor Regency for the 2016-2020 period, either partially or simultaneously. The population of this study is the entire local revenue of Alor Regency with a sample of the total income of PPJ, PH, PR, and PAD in Alor Regency for the 2016-2020 period. Collecting data using documentation study. Data analysis used multiple linear regression with the t-test and F test as a benchmark for hypothetical decision making. The results showed that partially PPJ had a significant t-test value of 0.039; partially PH has a significant value of t-test of 0.009. Partially, PR has a significance value of 0.007. The significance value of the t-test of PPJ, PH, and PR variables is smaller than the alpha value (0.05) so PPJ, PH, and PR have a significant positive effect on PAD in Alor Regency. The significance value of the F test of 0.000 is smaller than the alpha value (0.005) so that simultaneously PPJ, PH, and PR have a significant positive effect on PAD in Alor Regency.